Gastric Cancer Surgery Before and During the COVID-19 Pandemic in Turkey: A Multicenter Comparison of Prognostic Factors, Mortality, and Survival - Dalda, Yasin; Akbulut, Sami; Ogut, Zeki; Yilmaz, Serkan; Sahin, Emrah; Dalda, Ozlem; Kucukakcali, Zeynep (Mdpi, 2025)
Background/Objectives: The COVID-19 pandemic disrupted global cancer care. This study compared gastric cancer surgical outcomes before and during the pandemic in Turkey. We also aimed to analyze the impact of the pandemic and factors on survival and mortality in gastric cancer patients. Materials and Methods: This retrospective, multicenter cohort study included 324 patients from three tertiary centers in Turkey who underwent gastric cancer surgery between January 2018 and December 2022. Patients were stratified into Pre-COVID-19 (n = 150) and COVID-19 Era (n = 174) groups. Comprehensive demographic, surgical, pathological, and survival data were analyzed. To identify factors independently associated with postoperative mortality, a multivariable logistic regression model was applied. For evaluating predictors of long-term survival, multivariable Cox proportional hazards regression analysis was conducted. Results: The median time from diagnosis to surgery was comparable between groups, while the time from surgery to pathology report was significantly prolonged during the pandemic (p = 0.012). Laparoscopic surgery (p = 0.040) and near-total gastrectomy (p = 0.025) were more frequently performed in the Pre-COVID-19 group. Although survival rates between groups were similar (p = 0.964), follow-up duration was significantly shorter in the COVID-19 Era (p < 0.001). Comparison between survivor and non-survivor groups showed that several variables were significantly associated with mortality, including larger tumor size (p < 0.001), greater number of metastatic lymph nodes (p < 0.001), elevated preoperative CEA (p = 0.001), CA 19-9 (p < 0.001), poor tumor differentiation (p = 0.002), signet ring cell histology (p = 0.003), lymphovascular invasion (p < 0.001), and perineural invasion (p < 0.001). Multivariable logistic regression identified total gastrectomy (OR: 2.14), T4 tumor stage (OR: 2.93), N3 nodal status (OR: 2.87), and lymphovascular invasion (OR: 2.87) as independent predictors of postoperative mortality. Cox regression analysis revealed that combined tumor location (HR: 1.73), total gastrectomy (HR: 1.56), lymphovascular invasion (HR: 2.63), T4 tumor stage (HR: 1.93), N3 nodal status (HR: 1.71), and distant metastasis (HR: 1.74) were independently associated with decreased overall survival. Conclusions: Although gastric cancer surgery continued during the COVID-19 pandemic, some delays in pathology reporting were observed; however, these did not significantly affect the timing of adjuvant therapy or patient outcomes. Importantly, pandemic timing was not identified as an independent risk factor for mortality in multivariable logistic regression analysis, nor for survival in multivariable Cox regression analysis. Instead, tumor burden and aggressiveness-specifically advanced stage, lymphovascular invasion, and total gastrectomy-remained the primary independent determinants of poor prognosis. While pandemic-related workflow delays occurred, institutional adaptability preserved oncologic outcomes.
Keywords: gastric cancer; COVID-19 pandemic; prognostic factors; tumor staging; mortality; survival analysis